2016
DOI: 10.1016/j.celrep.2016.03.080
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing of Neuronal Differentiation Factor TRF2 Regulated by HNRNPH1/H2

Abstract: SUMMARY During neuronal differentiation, use of an alternative splice site on the rat telomere repeat-binding factor 2 (TRF2) mRNA generates a short TRF2 protein isoform (TRF2-S) capable of derepressing neuronal genes. However, the RNA-binding proteins (RBPs) controlling this splicing event are unknown. Here, using affinity pulldown analysis, we identified HNRNPH (heterogeneous nuclear ribonucleoprotein H) proteins as RBPs specifically capable of interacting with the spliced RNA segment (exon 7) of Trf2 pre-mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 41 publications
0
48
0
1
Order By: Relevance
“…While studying this question, we discovered a C-terminal truncated TRF2 splicing isoform (TRF2-S) that was expressed as neurons differentiated and grew their axons and dendrites, 17 and 5 years later we identified the splicing factor HNRNPH as being important for regulating neuronal TRF2 alternative splicing. 18 We also reported recently that instead of telomeric DNA, TRF2-S displayed a preference for binding RNA, and that TRF2-S is present in axons where it regulated mRNA trafficking. 19 In the present Extra Views, we briefly review the distinct functions of the nuclear, telomere-protective TRF2, and the cytoplasmic RNA-regulatory TRF2-S. We discuss the generation of the two TRF2 splicing isoforms and the role of HNRNPH in regulating the production of TRF2 in neural stem cells (NSCs) and TRF2-S in mature neurons.…”
Section: Regulation Of Trf2 Splicing and Function During Neurogenesismentioning
confidence: 99%
See 3 more Smart Citations
“…While studying this question, we discovered a C-terminal truncated TRF2 splicing isoform (TRF2-S) that was expressed as neurons differentiated and grew their axons and dendrites, 17 and 5 years later we identified the splicing factor HNRNPH as being important for regulating neuronal TRF2 alternative splicing. 18 We also reported recently that instead of telomeric DNA, TRF2-S displayed a preference for binding RNA, and that TRF2-S is present in axons where it regulated mRNA trafficking. 19 In the present Extra Views, we briefly review the distinct functions of the nuclear, telomere-protective TRF2, and the cytoplasmic RNA-regulatory TRF2-S. We discuss the generation of the two TRF2 splicing isoforms and the role of HNRNPH in regulating the production of TRF2 in neural stem cells (NSCs) and TRF2-S in mature neurons.…”
Section: Regulation Of Trf2 Splicing and Function During Neurogenesismentioning
confidence: 99%
“…Among the RBPs that were pulled down from rodent brain lysate, HNRNPH1 and HNRNPH2 (2 highly conserved proteins, >95%) positively regulated exon 7 inclusion and inhibited TRF2-S production, although HNRNPH1 appeared to suppress splicing and TRF2-S production more robustly. 18 Crosslinking and immunoprecipitation revealed that human HNRNPH1 also bound TRF2 pre-mRNA, and that the binding sequence was a G-rich tract containing A residues. 53,54 HNRNPH binding sites on and near exon 7 were further identified using in vitro binding assays.…”
Section: Nuclear Role Of Trf2mentioning
confidence: 99%
See 2 more Smart Citations
“…Both the RIP-seq data and depletion studies point to functions in axonal growth for hnRNP H1, F, and K. It will be of high interest to determine the molecular mechanisms for growth promotion by these hnRNPs and distinguish nuclear and somatic vs. axonal functions for these proteins. A few hnRNPs have been shown to impact neuronal differentiation and axon development (55)(56)(57). However, no studies have considered subcellular functions for these hnRNPs.…”
Section: Sj Lee Et Al Rna-protein Interactions For Axonal Mrnasmentioning
confidence: 99%